2023
DOI: 10.1002/adtp.202200332
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids: Momentous Tools in Transdermal Delivery of Biomacromolecules

Abstract: Transdermal drug delivery is a promising strategy characterized by minor fluctuations in blood concentrations, few adverse effects, convenience, and excellent patient compliance, especially for biomacromolecules. Conversely, traditional delivery methods are limited by their poor penetration abilities and complex preparation and application techniques. However, some inherent properties of biomacromolecules, such as large sizes, complex structure, and poor stability, can affect their ability to overcome skin bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 188 publications
0
5
0
Order By: Relevance
“…Most drugs are weak acidic or alkaline, and their water solubility is poor, which is the main obstacle in the development of new drug formulations. In this context, the ILs increase the solubility of insoluble small molecules and biomolecules, elevating their potential for drug delivery ( Table 5 ) [95] , [96] , [97] .…”
Section: Roles and Mechanismsmentioning
confidence: 99%
“…Most drugs are weak acidic or alkaline, and their water solubility is poor, which is the main obstacle in the development of new drug formulations. In this context, the ILs increase the solubility of insoluble small molecules and biomolecules, elevating their potential for drug delivery ( Table 5 ) [95] , [96] , [97] .…”
Section: Roles and Mechanismsmentioning
confidence: 99%
“…A careful selection of materials and a thorough evaluation of their cytotoxicity is necessary to ensure the safety of the transdermal delivery system. Additionally, the use of polyethylene glycol diacrylate (PEGDA) microneedles have shown good biocompatibility and successful transdermal delivery of small-molecule drugs. , …”
Section: Delivery Challenges Of Ampsmentioning
confidence: 99%
“…Additionally, the use of polyethylene glycol diacrylate (PEGDA) microneedles have shown good biocompatibility and successful transdermal delivery of small-molecule drugs. 197,203 Regulatory aspects play a significant role in the development and approval of transdermal delivery systems for AMPs. Regulatory agencies have specific guidelines and requirements for evaluating the safety, efficacy, and quality of transdermal drug delivery systems.…”
Section: Delivery Challenges Of Ampsmentioning
confidence: 99%
“…ILs with symmetrical structures have higher fluorescence quantum yield owing to the enhanced π–π* conjugation. Owing to the excellent hydrophilicity and strong fluorescence properties of some ILs, they are expected to be novel fluorescent probes [ 21 , 22 ] with high selectivity and sensitivity in the sensing and detection of biomacromolecules [ 23 ], oil field development [ 24 ], electrochemistry [ 25 ], medicine [ 26 ] and other directions. Gan found that due to the tunability of ILs, a new fluorescent IL probe [P66614][HQS] was designed, synthesised and characterised owing to the introduction of specific fluorophores into ILs.…”
Section: Introductionmentioning
confidence: 99%